2017
DOI: 10.1038/ncomms14612
|View full text |Cite
|
Sign up to set email alerts
|

Misrouting of v-ATPase subunit V0a1 dysregulates lysosomal acidification in a neurodegenerative lysosomal storage disease model

Abstract: Defective lysosomal acidification contributes to virtually all lysosomal storage disorders (LSDs) and to common neurodegenerative diseases like Alzheimer's and Parkinson's. Despite its fundamental importance, the mechanism(s) underlying this defect remains unclear. The v-ATPase, a multisubunit protein complex composed of cytosolic V1-sector and lysosomal membrane-anchored V0-sector, regulates lysosomal acidification. Mutations in the CLN1 gene, encoding PPT1, cause a devastating neurodegenerative LSD, INCL. He… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

6
161
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 134 publications
(167 citation statements)
references
References 68 publications
(131 reference statements)
6
161
0
Order By: Relevance
“…Recently the regulation of V-ATPase localization by PPT1 was described in neurons (27). The amino acid-dependent physical interaction between vATPase and the Ragulator complex facilitates the lysosomal recruitment of mTORC1 by Rag GTPases (28).…”
Section: Resultsmentioning
confidence: 99%
“…Recently the regulation of V-ATPase localization by PPT1 was described in neurons (27). The amino acid-dependent physical interaction between vATPase and the Ragulator complex facilitates the lysosomal recruitment of mTORC1 by Rag GTPases (28).…”
Section: Resultsmentioning
confidence: 99%
“…We sought to determine the cause of increased lysosomal pH in JNCL fibroblasts. Previously, we reported that Ppt1‐deficiency leads to the misrouting of the V0a1 subunit of the v‐ATPase to the plasma membrane dysregulating lysosomal pH in cultured neurons from Cln1 −/− mice . Thus, we sought to determine whether Cln3 ‐mutations causing PPT1 insufficiency in cultured JNCL fibroblasts V0a1 is mislocalized to the plasma membrane and not to its normal location on lysosomal membrane.…”
Section: Resultsmentioning
confidence: 99%
“…Lysosomal acidification is regulated by v‐ATPase, a multi‐subunit protein localized to the lysosomal membrane. Previously, we reported that in Cln1 −/− mice, which mimic INCL and in cultured fibroblasts from INCL patients, PPT1‐deficiency causes misrouting of a critical subunit of v‐ATPase, V0a1, to the plasma membrane instead of its normal location to the lysosomal membrane dysregulating lysosomal acidification . Thus, we first sought to determine whether lysosomal pH is dysregulated in cultured JNCL patient fibroblasts.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…[45][46][47] The pathophysiological roles of FAIM2 in the nervous system would be of interest. Other molecules may substitute FAIM2 function in cells not expressing FAIM2.…”
Section: Discussionmentioning
confidence: 99%